A positive experience in applying the biolistic approach to potato varieties Aksor and Nevskiy - N. P. Malakhova; Y. A. Skiba; G. A. Iskakova; D. A. Naizabayeva; B. K. Tezekbaeva; G. A. Ismagulova; E. R. Maltseva (Вавиловский журнал генетики и селекции)
The method of biological ballistics (biolistic transformation, genetic bombardment) of plants is one of the most modern methods used for direct gene transfer into plant cells. The main advantages of this method include the ability to simultaneously incorporate several target genes into the plant genome, carry out transfer without unnecessary agrobacterial parts and plasmid DNA sequences, and the short time needed to produce transgenic cells. For different plant objects, the efficiency of obtaining transgenic plants by the ballistic method varies from 1 to 3 %. For potato plants, the transformation efficiency is quite low at the moment and the selection of optimal conditions for biolistics is one of the pressing issues of practical biotechnology. This article presents a successful experience of introducing two genes of interest into two potato varieties using the biolistic approach. The results of biolistic transformation experiments are presented for two types of explants: potato internodes and calli of the varieties Aksor and Nevskiy. Of the 862 explants used for transformation, 56 regenerated plants were obtained. PCR screening of transformants revealed one plant with the insertion of the chitinase gene, one with the insertion of the endo-β-1,3-glucanase gene, and co-transformation by both genes was confirmed in four regenerants. The average transformation efficiency for potato explants was 0.7 %. A high number of regenerants (56) as opposed to a low number of transformants (6) reflects an attempt to increase the number of regenerants by using a lower concentration of the selective agent (kanamycin). Although this approach requires more effort, it can be used to produce potato lines with integrated genes of interest for further use in crop breeding. The lines of potato obtained in the current study by introducing two genes associated with the plant response to fungal pathogens will be further assessed for their resistance to fungal diseases and, if successful, will be used in potato crop breeding.